Phase I Study To Evaluate the Pharmacokinetics, Safety, and Tolerability of Two Dosing Regimens of Oral Fosfomycin Tromethamine in Healthy Adult Participants - Wenzler, Eric; Bleasdale, Susan C.; Sikka, Monica; Bunnell, Kristen L.; Finnemeyer, Matthew; Rosenkranz, Susan L.; Danziger, Larry H.; Rodvold, Keith A. (Antimicrobial agents and chemotherapy, 2018)
The pharmacokinetics (PK), safety, and tolerability of two repeated dosing regimens of oral fosfomycin tromethamine were evaluated in 18 healthy adult subjects. Subjects received 3 g every other day (QOD) for 3 doses and then every day (QD) for 7 doses, or vice versa, in a phase I, randomized, open-label, two-period-crossover study. The pharmacokinetics (PK), safety, and tolerability of two repeated dosing regimens of oral fosfomycin tromethamine were evaluated in 18 healthy adult subjects. Subjects received 3 g every other day (QOD) for 3 doses and then every day (QD) for 7 doses, or vice versa, in a phase I, randomized, open-label, two-period-crossover study. Serial blood ( n = 11) and urine ( n = 4 collection intervals) samples were collected before and up to 24 h after dosing on days 1 and 5, along with predose concentrations on days 3 and 7. PK parameters were similar between days 1 and 5 within and between dosing regimens. The mean (± standard deviation [SD]) PK parameters for fosfomycin in plasma on day 5 during the respective QOD and QD dosing regimens were as follows: maximum concentration of drug in serum ( C max ) = 24.4 ± 6.2 versus 23.8 ± 5.6 μg/ml, time to C max ( T max ) = 2.2 ± 0.7 versus 2.0 ± 0.4 h, apparent volume of distribution ( V / F ) = 141 ± 67.9 versus 147 ± 67.6 liters, apparent clearance (CL/ F ) = 21.4 ± 8.0 versus 20.4 ± 5.3 liters/h, renal clearance (CL R ) = 7.5 ± 4.1 versus 7.3 ± 3.5 liters/h, area under the concentration-time curve from 0 to 24 h (AUC 0–24 ) = 151.6 ± 35.6 versus 156.6 ± 42.5 μg · h/ml, and elimination half-life ( t 1/2 ) = 4.5 ± 1.1 versus 5.0 ± 1.7 h. Urine concentrations peaked at approximately 600 μg/ml through the 0- to 8-h urine collection intervals but displayed significant interindividual variability. Roughly 35 to 40% of the 3-g dose was excreted in the urine by 24 h postdose. No new safety concerns were identified during this study. The proportion of diarrhea-free days during the study was significantly lower with the QD regimen than with the QOD regimen (61% versus 77%; P < 0.0001). Further studies to establish the clinical benefit/risk ratio for repeated dosing regimens of oral fosfomycin tromethamine are warranted. (This trial is registered at ClinicalTrials.gov under registration no. NCT02570074.)